Obesity is associated with impaired postprandial pancreatic polypeptide secretion - Zhao, Yanyun; Zhou, Yue; Chi, Jingwei; Che, Kui; Wang, Yangang; Wang, Wei (Frontiers in Endocrinology, 2023)
Objective: This study aims to compare the levels of serum pancreatic polypeptide (PP), insulin (INS), C-peptide (C-P), and glucagon (GCG) before and after glucose stimulation in type 2 diabetes mellitus (T2DM) patients with different body mass index (BMI), analyze the relevant factors associated with PP secretion, and further investigate the role of PP in the development of obesity and diabetes. Methods: Data were collected from 83 patients from the hospital. The subjects were divided into normal-weight group, overweight group, and obese group according to their BMI. All subjects were tested with the standard bread meal test (SBMT). PP and relevant parameters were measured, and the area under the curve (AUC) was calculated after 120 minutes of SBMT. AUCpp (AUC of PP) was used as the dependent variable, and the potential influencing factors were used as independent variables for multiple linear regression analysis. Results: The obese and overweight groups had significantly lower PP secretion than the normal-weight group (485.95pg·h/mL, 95%CI 76.16-895.74, p=0.021; 664.61pg·h/mL, 95%CI 285.46-1043.77, p=0.001) at 60 minutes postprandial. PP secretion in the obese and overweight groups were also significantly lower than that in the normal-weight group (520.07pg·h/mL, 95%CI 186.58-853.56, p=0.003; 467.62pg·h/mL, 95%CI 159.06-776.18, p=0.003) at 120 minutes postprandial. AUCpp was negatively associated with BMI (r=-0.260, p=0.017) and positively associated with AUCGCG (r=0.501, p<0.001). Multiple linear regression analysis showed that there was a linear correlation between AUCGCG, BMI, and AUCpp(p<0.001, p=0.008). The regression equation was calculated as follows: AUCpp=1772.255-39.65×BMI+0.957×AUCGCG (R2 = 54.1%, p<0.001). Conclusions: Compared with normal-weight subjects, overweight and obese subjects had impaired PP secretion after glucose-stimulation. In T2DM patients, PP secretion was mainly affected by BMI and GCG.